Pelanggaran Maksim Kesopanan Dalam Kolom Komentar Twitter Joko Widodo - Kunti Zahrotun Alfi; Farida Yufarlina Rosita (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2019)
Communicating or interacting basically becomes human needs as social beings. The communication process occurs if there are speakers and opponents to say in it, both directly and written. The written communication process in the present era is a need that cannot be separated from people's lives. Various writing media continue to vary as the development of technology and communication facilitates the written communication process. The ease of written communication makes one can give comments or opinions to others. Some of these comments become new phenomena as a way of criticizing someone through written media so that the words or sentences used are not polite. Through this phenomenon, this study will discuss the violation of the principle or maxims of modesty that are in Joko Widodo's twitter comment column. The method in this study is descriptive qualitative. The data source is written data. The data collection technique uses the refer method, which is listening to the use of language in the comments column on Joko Widodo's twitter. The technique for collecting data is used, namely the recording technique. The researcher uses a recording device on the cellphone (cellphone) by means of screen capturing (screenshot) in Joko Widodo's twitter comment column, then the researcher records the data in the form of text and classifies it. The results of the study indicate that violations of maxims are found in the maxims of agreement. The causes of courtesy violations are due to several reasons, including: (1) disagreement with, (2) political contestation, and (3) feeling better.